Revitalisasi Digital Pepak Bahasa Jawa Melalui Aplikasi Jawa Jaya Sebagai Modul Ajar Pendamping Siswa Menggunakan Pengujian SUS - Subrata, Febrina Cinta; Mardhiyyah, Rodhiyah (Journal of Information System Research (JOSH), 2025)
The declining interest in learning Javanese among primary and secondary school students is the focus of government and educator evaluation, as it is important to maintain the sustainability of the use of regional languages as an integral part of Indonesia's cultural identity. The still conservative nature of Javanese language learning is a consideration for the digitisation of teaching modules. The revival of Javanese pepak aims to revive the cultural wealth contained in various linguistic and literary aspects, such as tembang macapat, folk legends and the unggah-ungguh basa system, which reflects manners in communication. As Javanese culture itself is closely linked to the value system, philosophy of life and social norms, efforts to preserve it through technological innovation are very relevant. By applying the Content Structuring & Delivering by Modular Learning method, this application presents various features such as automatic translation, Javanese language levels (ngoko, madya and krama) and interactive quizzes, which can expand the accessibility of Javanese language learning. So far, a Javanese language (Pepak) learning support module in the form of an application is still not common. Therefore, this research aims to respond to these needs by developing a digital platform that will become one of the students' access points in learning Javanese through mobile devices. In this study, the application was developed using the Kotlin programming language with a localhost database, MySQL. System Usability Scale (SUS) test results show that the Jawa Jaya application is in the Acceptable (High) category with an adjective rating of Good and a score of 72.